PENGARUH RETURN ON ASSETS (ROA), NET PROFIT MARGIN (NPM), DAN EARNING PER SHARE (EPS) TERHADAP HARGA SAHAM PADA PERUSAHAAN PERBANKAN DI BURSA EFEK INDONESIA PERIODE 2018-2022 - Fariz Mustaqim; La Ode Abdul Rakhman; Aprylia Ode; Ahmad Daholu (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM, 2024)
This study aims to determine the effect of return on assets, net profit margin and earning per share on stock prices in banking companies listed on the Indonesia Stock Exchange. The research method uses quantitative descriptive analysis & multiple linear regression analysis. Data collection using the company's financial statements and processed with the SPSS version 25 application. The results showed that partially, Return on assets (ROA) had no effect on stock prices, which was seen from the significance value of the partial test results, namely with a significant value of 0.205> 0.05. The Net profit margin (NPM) variable has a positive effect on stock prices, as seen from the significance value of the partial test results, namely with a significant value of 0.024 <0.05. Earning per share (EPS) variable has a positive effect on stock prices, as seen from the significance value of the partial test results, namely with a significant value of 0.000 <0.05. Simultaneously, all independent variables (bound) have a significant effect on investment decisions with a significant value of 0.000 less than 0.005.